Peran Sosiologi Pendidikan dalam Membentuk Sikap Kepedulian Sosial Siswa di Sekolah - Puput Rifani; Nur Khasanah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
Sociology of education is a field that examines the relationship between education and social life in society, focusing on how educational processes shape students’ character and social behavior. Schools function not only as places to acquire academic knowledge but also as social environments where students learn to interact, cooperate, respect differences, and develop social responsibility. This study aims to understand the role of sociology of education in shaping students’ social awareness within the school context, particularly in fostering empathy, cooperation, and social responsibility. A qualitative research approach was used to explore how learning sociology of education influences students’ attitudes and behaviors. The findings indicate that sociology of education plays an important role in developing students’ social awareness. Through this learning process, students gain a better understanding of social values, norms, and appropriate behavior in society. Teachers and schools contribute significantly by providing role models, building positive habits, and organizing activities that encourage caring attitudes toward others. As a result, schools become spaces not only for intellectual development but also for character formation. Observations at Misalova School show that students demonstrate increased social concern, such as collecting donations and visiting sick friends, providing assistance when school members experience disasters, and actively participating in social activities. In addition, students help one another in learning processes and cooperate in group activities without discrimination. Overall, learning sociology of education helps students develop social awareness, respect diversity, and contribute positively to their school and community environments.